Enhancing coal tailing quality by Flotation Method using Biosurfactant from Lerak (Sapindusrarak De Candole) - Danang Jaya; Tunjung Wahyu Widayati; Refina Yuni Mustika; Halim Nur Aziz Suwardi (Eksergi, 2020)
Wasted from coal mining that mixed with the wasted of the coal washing product called Coals Tailing (CT) has a low calorific value,high sulfur and ash content. To upgrade its quality by increasing its calorific value and to reduce environmental pollution by reducing sulfur and its ashes, coal must improve from its impurities, one of which is to try with flotation method. Flotation is a process that describes solids that occur due to differences in surface properties (surface properties). The flotation process takes place in a system consisting of three phases, namely gas phase, liquid, and solid, which are interrelated to complete the appearance (with the help of flotation agent  /  surfactant)  so  that  discussion  occurs  between  the  hydrophobic  component  (waterproof)  and  the hydrophilic component (like water). The main objective of the research is to improve the quality of coals tailing (CT), by increasing the calorific value (reducing the content of sulfur, ash, and other impurities) using the flotation method, and using lerak (Sapindus rarak De Candole) as a surfactant. From this research show that an optimal conditions were obtained, at particle size of -80 / + 100 mesh, operating conditions at pH 6, calorific value increased from initially 3230,171 cal/gr to 5035,622 cal/gr, sulfur content decreased according to   the optimum condition reached 2026.08 mg /kg, and the ash content decreased from 54.61% to 33.9%. From the results of these research indicate, Lerak as a surfactant is is enhanced to improve the quality of Tailings Coal (CT) by flotation method.